2019
DOI: 10.3390/ijms20122923
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analyses of mRNA Expression Profile Reveal the Involvement of IGF2BP1 in Chicken Adipogenesis

Abstract: Excessive abdominal fat deposition is an issue with general concern in broiler production, especially for Chinese native chicken breeds. A high-fat diet (HFD) can induce body weight gained and excessive fat deposition, and genes and pathways participate in fat metabolism and adipogenesis would be influenced by HFD. In order to reveal the main genes and pathways involved in chicken abdominal fat deposition, we used HFD and normal diet (ND) to feed a Chinese native chicken breed, respectively. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…However, in-depth studies on the functions of chicken circFNDC3AL and circHSPG2 on adipogenic differentiation are essential. Previous research reported that runtrelated transcription factor 1 (RUNX1T1) [42,43], myosin, heavy chain 9, non-muscle (MYH9), fatty acid desaturase 2 (FADS2), insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1) were associated with adipogenesis and fat deposition [44][45][46][47]. We found that circLCLAT1 might influence adipogenic differentiation by regulating downstream genes (RUNX1T1, FADS2, MYH9, IGF2BP3, and PDGFRA) through four miRNAs (miR-34a-5p, miR-30e-5p, miR-146b-5p, and miR-147).…”
Section: Discussionmentioning
confidence: 99%
“…However, in-depth studies on the functions of chicken circFNDC3AL and circHSPG2 on adipogenic differentiation are essential. Previous research reported that runtrelated transcription factor 1 (RUNX1T1) [42,43], myosin, heavy chain 9, non-muscle (MYH9), fatty acid desaturase 2 (FADS2), insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1) were associated with adipogenesis and fat deposition [44][45][46][47]. We found that circLCLAT1 might influence adipogenic differentiation by regulating downstream genes (RUNX1T1, FADS2, MYH9, IGF2BP3, and PDGFRA) through four miRNAs (miR-34a-5p, miR-30e-5p, miR-146b-5p, and miR-147).…”
Section: Discussionmentioning
confidence: 99%
“…However, indepth studies on the functions of chicken circFNDC3AL and circHSPG2 on adipogenic differentiation are essential. Previous research reported that runt-related transcription factor 1 (RUNX1T1) [42,43], myosin, heavy chain 9, non-muscle (MYH9), fatty acid desaturase 2 (FADS2), insulin-like growth factor 2 mRNAbinding protein 1 (IGF2BP1) were associated with adipogenesis and fat deposition [44][45][46][47]. We found that circLCLAT1 might in uence adipogenic differentiation by regulating downstream genes (RUNX1T1, FADS2, MYH9, IGF2BP3, and PDGFRA) through four miRNAs (miR-34a-5p, miR-30e-5p, miR-146b-5p, and miR-147).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies need to be done to investigate the functions of chicken circFNDC3AL and circHSPG2 on adipogenic differentiation. Previous studies reported that runt-related transcription factor 1 (RUNX1T1) [42,43], myosin, heavy chain 9, nonmuscle (MYH9), fatty acid desaturase 2 (FADS2), insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1) [44][45][46][47] were associated with adipogenesis and fat deposition. We found that circLCLAT1 might affect adipogenic differentiation by regulating downstream genes (RUNX1T1, FADS2, MYH9, IGF2BP1 and PDGFRA) via four miRNAs (miR-34a-5p, miR-30e-5p, miR-146b-5p and miR-147).…”
Section: Discussionmentioning
confidence: 99%